A prospective evaluation of microscale thermophoresis coupled with mass spectrometry using the “RGB_ex-ante” model - Paweł Mateusz Nowak; Aleksandra Zima; Małgorzata Gołąb; Michał Woźniakiewicz (Green Analytical Chemistry)
The evaluation of greenness and whiteness is usually made retrospectively (ex-post) – for a developed and validated methodology ready for use. However, it can also be made ex-ante, i.e. taking into account the potential pros and cons that have not yet been experimentally confirmed. The RGB_ex-ante model presented here is a simple assessment framework to help determine whether developing a new specific methodology is worth investing effort. We used it for a prospective evaluation of a new foreseen technique – microscale thermophoresis (MST) coupled online with mass spectrometry (MST-MS). Concurrently, it was demonstrated that biophysical techniques dedicated to the analysis of biomolecular interactions, such as MST, can and should be assessed in terms of greenness and whiteness on an equal footing with chromatography, spectroscopy and other quantitative analysis techniques. We report the original preliminary research results confirming the possibility of combining online MST and MS instruments, which, however, do not yet constitute evidence for analyzing equilibrium processes in this system. For that reason, an ex-ante evaluation was performed. The obtained greenness and whiteness scores suggest that the MST-MS technique would likely be greener than the conventional offline approach, but not whiter. Despite some potential benefits related to all attributes (red, green and blue criteria), the implementation of MST-MS coupling would entail a number of limitations that overall offset the expected merits. The proposed evaluation model turned out to be a simple and helpful tool that is worth using prior developing new methods, procedures and experimental techniques in analytical laboratory and beyond.